Neuro-educación como alternativa para cuidadores de paciente con trauma (2013)
The neuro-education could be a strategy that can be used not only in people who have had a trauma but also caregivers, considering that help the rehabilitation process and the patient's social foray to lessen the risks affective, somatization, physical tiredness may suffer their family and psychosocial environment and improve its forecast expectations, for this reason this paper seeks to clarify the proposal of this strategy in patients who are in the recovery phase of their disease and may contribute to mental health.